Ayuntamiento a colonial legacy as national heritage - Alfonso, Ian Christopher (2016)
This paper attempts to rewrite the history of the recently reconstructed Ayuntamiento building in Intramuros, Manila in a more nationalist perspective. The Ayuntamiento boasts its extraordinary role in the history of the Filipino's struggle for complete soveeignty as it served as palace for the executive, legislative, and judiciary branches from 1899 to 1945. Theses milestones in those formtive years of the naton were a continuation of what had been declared at Balintawak, proclaimed at Aguinaldo's house, and chartered at the Barasoain Church-- the Revolution, the Independence, and the Republic, the firsts in Asia. This kind of perspective rationalizes further the saysay (sense) to the people of a colonial legacy as part of their own inheritance and a source of national identity.
Keywords: Heritage buildings; Ayuntamiento Building (Intramuros, Manila)